Assessing of Pedagogical Competency of Prospective Teachers in Teaching Arabic in Schools: Suitable or not Suitable? - Sauri, Sofyan; Sanusi, Anwar (Journal of Ecohumanism, 2024)
Pedagogical competency is the starting point for prospective Arabic language teachers to master the learning process. However, the prospective Arabic language has not yet fully mastered pedagogical competence. Through this research, researchers want to see the suitability of prospective Arabic language teachers by pedagogical competency standards by the Regulation of the Minister of National Education of the Republic of Indonesia No. 16 of 2007 concerning Academic Qualification Standards and Teacher Competencies. This research used a mixed-method approach with participants from Indonesia and Malaysia. Researchers then compare the advantages and disadvantages according to predetermined standards. The research results show prospective Arabic language teachers in Indonesia and Malaysia can utilize digital-based learning media. However, prospective Arabic language teachers from Indonesia still need to gain the skills to use Arabic actively during the learning process. In contrast, prospective Arabic language teachers from Malaysia already have sufficient skills.